Analisis Kinerja Keuangan Dan Pengaruhnya Terhadap Harga Saham (Studi Kasus Pada Pt Aqua Golden Mississippi, Tbk Sebelum Akuisisi Saham Dan Sesudah Akuisisi Saham Oleh Danone Periode Tahun 1997 2007) - Entar Sutisman; Sad Lingga Fitriana; Dianwicaksih Arieftiara (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractThis research destination is to understand something effect from financial performance to corporate stock price before acquisition and after acquisition. Selected which corporate is PT Aqua Golden Mississippi, Tbk with measuring instrument z score analysis Taffler model as measuring instrument corporate financial performance and linear regretion to understand something effect from financial performance to stock price with period 1997 2007 be based on corporate year after and before acquisition. That indicate from analysis revenue corporate financial performance after and before acquisition significant influence stock price, but just direction relationship which different. This matter because of there are other factor factor which influence stock price, one of them is corporate drinking water in package stock not likuid in stock exchange. On the contrary, corporate condition after acquisition not significant, this meaning is increase of financial performance not followed with the increasing of corporate stock price